THE PRINCIPAL LEADERSHIP IN IMPROVING TEACHERS' TEACHING CREATIVITY AT MTS AL WATHON PURWAKARTA. - Syarifudin, Denden; Saepuloh, Saepuloh (ASWAJA: Jurnal Pendidikan dan Keislaman, 2026)
The purpose of this study was to determine the principal's leadership performance in enhancing teaching creativity and its influence on teacher creativity. This study used a qualitative descriptive approach, with the principal as the primary informant and teachers as supporting informants. Data were collected through interviews, observation, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. Data validity was tested using source triangulation, time triangulation, and technical triangulation. The results showed that the principal of MTs Al-Wathon Purwakarta implemented a democratic leadership style to enhance teacher teaching creativity. This was reflected in the principal's ability to lead, integrate human resources, and create a work climate in accordance with National Education Standards. Teacher teaching creativity was proven to increase when school leadership aligned with teacher expectations and was supported by internal and external factors, such as the principal's leadership habits, the provision of praise and rewards, and opportunities for teacher development through workshops and seminars. The principal's leadership also impacted teachers' enthusiasm and motivation to become professional educators, serving as role models, creating stress-free working relationships, and improving student achievement in both academic and non-academic aspects.